Anti-tumor activity of phenoxybenzamine and its inhibition of histone deacetylases. - Mario A Inchiosa (PLoS ONE)
The principal finding from this study was the recognition that the α-adrenergic antagonist, phenoxybenzamine, possesses histone deacetylase inhibitory activity. Phenoxybenzamine is approved by the United States Food and Drug Administration for the treatment of hypertensive crises associated with tumors of the adrenal medulla, pheochromocytomas. It has several "off label" indications relative to its capacity to relax vascular smooth muscle and smooth muscle of the urogenital tract. The drug also has a long history of apparent efficacy in ameliorating, and perhaps reversing, the severe symptoms of neuropathic pain syndromes. Our interest in this feature of the drug relates to the fact that certain types of neuropathic pain, in particular complex regional pain syndrome, demonstrate a proliferative nature, with the capacity to spread from an injured limb, for example, to a non-injured limb and perhaps to essentially the entire body. Sensory neuronal sprouting in the spinal cord has been observed under conditions where there is a high sensory input from painful stimuli. Searches of gene expression signatures in the BroadBuild02 Molecular Signature Database using their connectivity map software suggested that phenoxybenzamine may have histone deacetylase inhibitory activity. Studies by others have reported inhibitory effects of phenoxybenzamine on growth, invasion and migration of human tumor cell cultures and, in one study, inhibition of tumor expansion in animal experiments. Inhibitory effects on human tumor cell cultures are also reported in the present study. Phenoxybenzamine was also found to have histone deacetylase inhibitory activity; histone deacetylase isoforms 5, 6, and 9 were the most sensitive to inhibition by phenoxybenzamine. The importance of elevated levels of these isoforms as biomarkers of poor prognosis in human malignant disease, and the recognized suppression of tumor growth that may accrue from their inhibition, opens consideration of possible translation of phenoxybenzamine to new clinical applications. This might be facilitated by the fact that phenoxybenzamine is already an approved drug entity. There appears to be no previous report of the activity of phenoxybenzamine as a histone deacetylase inhibitor.